Social wasps are effective biocontrol agents of key lepidopteran crop pests - Southon, Robin J.; Fernandes, Odair A. [UNESP]; Nascimento, Fabio S.; Sumner, Seirian (The Royal Society, 2019)
Biocontrol agents can help reduce pest populations as part of an integrated pest management scheme, with minimal environmental consequences. However, biocontrol agents are often non-native species and require significant infrastructure; overuse of single agents results in pest resistance. Native biocontrol agents are urgently required for more sustainable multi-faceted approaches to pest management. Social wasps are natural predators of lepidopteran pests, yet their viability as native biocontrol agents is largely unknown. Here, we provide evidence that the social paper wasp Polistes satan is a successful predator on the larvae of two economically important and resilient crop pests, the sugarcane borer Diatraea saccharalis (on sugarcane Saccharum spp.) and the fall armyworm Spodoptera frugiperda (on maize Zea mays); P. satan wasps significantly reduce crop pest damage. These results provide the much-needed baseline experimental evidence that social wasps have untapped potential as native biocontrol agents for sustainable crop production and food security.
Keywords: Biocontrol; Diatraea saccharalis; Integrated pest management; Paper wasps; Polistes satan; Spodoptera frugiperda